Islamiat for students book I - Farkhanda, Noor (Feroz sons Lahore, 2011)
This comprehensive book provides young learners with a clear understanding of Islamic teachings and principles. Through engaging content and relatable examples, it encourages students to reflect on their faith and its application in daily life. Ideal for fostering a strong moral foundation and appreciation for Islamic values.